Production Potential and Quality of Panicum maximum Cultivars Established in a Semi-Arid Environment - M. de G. Pereira; G. dos S. Difante; L. C. V. Ítavo; J. G. Rodrigues; A. L. C. Gurgel; A. M. Dias; C. C. B. F. Ítavo; E. L. de L. Veras; A. B. G. da Costa; G. O. de A. Monteiro (Tropical Animal Science Journal, 2022)
This study was conducted to examine the forage production potential and quality of Panicum maximum cultivars in a semi-arid environment, in four different periods. Six cultivars were evaluated: Aruana, Massai, Mombasa, BRS Tamani, Tanzania, and BRS Zuri. The experiment was laid out in a randomized-block design with four replicates, and assessments took place in four different periods (establishment, dry season, transition, and rainy season). Forage accumulation rate (FAR), chemical composition, digestibility, and in vitro rumen degradation kinetics were evaluated. There was an interaction effect between cultivars and evaluation periods for all variables, except dry matter (DM) content. The highest FAR occurred in cvs. BRS Tamani (47.0 kg DM/ha/day) and BRS Zuri (86.9 kg DM/ha/day) in the establishment and rainy periods, respectively, while cv. Aruana showed the lowest FAR (14.5 kg DM/ha/day). The highest crude protein contents were found in cv. BRS Tamani in the transition period; cv. BRS Zuri in the dry season; and cv. Tanzania in the rainy season (128.2, 116.7, and 95.0 g/kg DM, respectively). Cultivar Aruana showed the highest average in vitro dry matter digestibility (810.0 g/kg DM). Cultivars Aruana and Zuri exhibited the highest means of the total in vitro gas production (23.59 and 20.24 mL/100 mg DM, respectively). Cultivars BRS Tamani and BRS Zuri had the best response in terms of forage accumulation and nutritional value. The quality of cv. Massai remained constant throughout the year. All Panicum maximum cultivars evaluated here have the potential for use in animal production systems in a semi-arid environment.